Kata Fasad dalam Al Quran (Analisis Semantik Al Quran) - Ahmad Imam Hamimi; Lilik Rochmad Nurcholisho; Fatkhurrohman Fatkhurrohman; Nurul Ngazizah; Asep Sunarko (Lisanan Arabiya: Jurnal Pendidikan Bahasa Arab, 2022)
This study aims to find out the concept of the word Fasa>d in the Qur'an and the development of its meaning. The approach used is the semantic approach of the Qur'an proposed by Toshihiko Izutsu. The data sources of this research are the verses of the Qur'an which use the word fasa>d and its derivations as well as the verses of the Qur'an which have a similar meaning to the word fasa>d. The steps taken by the researcher in collecting data are as follows: First, collecting the verses of the Qur'an that contain the word fasa>d. Second, classifying verses. Third, analyzing the word fasa>d using focus word techniques, keywords, basic meanings, and relational meanings, synchronic and diachronic meanings, semantic fields, and weltanschauung, Fourth, drawing messages from the Qur'an. Fifth, drawing conclusions. The results of the research show that the word fasa>d with its various derivations is repeated 50 times in the Qur'an. Syntagmatically It means disobedience, destruction, drought/ withholding of rain, murder, corruption, and sorcerers, while paradigmatically, fasa>d has similarities with the words Syarr, Halaka or ahlaka , 'As\a>, Bat{ala , Sa>'a and Z}alama . Words that are opposite to the word fasa>d are As}laha, Ah}sana, Khair and, al-h}aqqu. This study also shows that even though the word fasa>d has experienced a development or expansion of meaning, it still refers to a single meaning, namely deviating from the path and containing a negative meaning.